DIALEKTIKA AL-JANNAH DAN AL-NĀR DALAM AL-QUR’AN SERTA IMPLIKASI DAN RELEVANSINYA UNTUK KEHIDUPAN KONTEMPORER: DIALEKTIKA AL-JANNAH DAN AL-NĀR DALAM AL-QUR’AN SERTA IMPLIKASI DAN RELEVANSINYA UNTUK KEHIDUPAN KONTEMPORER - Riv'atul Mahmudah; Alfi Julizun Azwar; Halimatussa’diyah (Jurnal Studi Qur'an dan Tafsir, 2025)
This study aims to examine the dialectic of Al-Jannah (heaven) and al-Nār (hell) in the Qur’an through the framework of Makkiyah and Madaniyyah theories, as well as to explore their implications and relevance for contemporary life. The focus lies in understanding how the Qur’an portrays heaven and hell as theological, moral, and social instruments that shape the character of believers. This research employs a library-based qualitative descriptive approach. The primary source is the Qur’an, while secondary sources include classical and modern exegesis such as Tafsir Al-Azhar by Hamka, Tafsir Al-Mishbah by Quraish Shihab, and Tafsir al-Baghawi. Data were analyzed using thematic exegesis (tafsir maudhu’i) combined with socio-historical analysis to reveal the differences between Makkiyah and Madaniyyah verses concerning heaven and hell. The findings indicate that the dialectic of heaven and hell goes beyond eschatological imagery, serving as ethical guidance that emphasizes moral cultivation, social justice, and Islamic spirituality. In the Makkiyah phase, al-Jannah is portrayed as motivation for faith and resilience, while al-Nār functions as a moral warning. In the Madaniyyah phase, both concepts highlight legal, social, and communal responsibilities.